Efficient decellularization for tissue engineering of the tendon-bone interface with preservation of biomechanics. - Kai Xu; Lara A Kuntz; Peter Foehr; Katharina Kuempel; Alexandra Wagner; Jutta Tuebel; Constantin V Deimling; Rainer H Burgkart (PLoS ONE)
Interfaces between tendon/ligament and bone ("entheses") are highly specialized tissues that allow for stress transfer between mechanically dissimilar materials. Entheses show very low regenerative capacity resulting in high incidences of failure after surgical repair. Tissue engineering is a promising approach to recover functionality of entheses. Here, we established a protocol to decellularize porcine entheses as scaffolds for enthesis tissue engineering. Chemical detergents as well as physical treatments were investigated with regard to their efficiency to decellularize 2 mm thick porcine Achilles tendon entheses. A two-phase approach was employed: study 1 investigated the effect of various concentrations of sodium dodecyl sulfate (SDS) and t-octylphenoxypolyethoxy-ethanol (Triton X-100) as decellularization agents. The most efficient combination of SDS and Triton was then carried forward into study 2, where different physical methods, including freeze-thaw cycles, ultrasound, perfusion, and hydrostatic washing were used to enhance the decellularization effect. Cell counts, DNA quantification, and histology showed that washing with 0.5% SDS + 1% Triton X-100 for 72 h at room temperature could remove ~ 98% cells from the interface. Further investigation of physical methods proved that washing under 200 mmHg hydrostatic pressure shortened the detergent exposing time from 72 h to 48 h. Biomechanical tensile testing showed that the biomechanical features of treated samples were preserved. Washing under 200 mmHg hydrostatic pressure with 0.5% SDS + 1% Triton X-100 for 48 h efficiently decellularized entheses with preservation of matrix structure and biomechanical features. This protocol can be used to efficiently decellularize entheses as scaffolds for tissue engineering.